2018
DOI: 10.1016/j.cardfail.2018.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Diastolic Dysfunction in Individuals With Human Immunodeficiency Virus Infection: Literature Review, Rationale and Design of the Characterizing Heart Function on Antiretroviral Therapy (CHART) Study

Abstract: Antiretroviral therapy (ART) has been associated with a shift in the epidemiology of human immunodeficiency virus (HIV)-associated cardiomyopathy from a phenotype of primarily left ventricular (LV) systolic dysfunction to LV diastolic dysfunction (DD). Patients with HIV receiving ART have higher rates of DD compared with age-matched control subjects and develop DD at a younger age. However, little is known about the natural history and pathogenesis of DD in virally suppressed HIV-infected patients. Current evi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
30
0
5

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 77 publications
0
30
0
5
Order By: Relevance
“…That study aims to establish clinical phenotypes of DD in persons with chronic HIV. 29 Finally, the cross-sectional nature of the present study does not address the potential evolution of ventricular dysfunction among PLWH and limits our ability to evaluate the future risk of the evolution of incident clinical heart failure. Although future studies of our cohort will focus on monitoring its members longitudinally to investigate the natural history of ventricular dysfunction in this group, a prospectively identified and followed longitudinal cohort is needed to explore and fully characterize the evolution and determinants of cardiac structural alterations in PLWH.…”
Section: Study Limitationsmentioning
confidence: 95%
“…That study aims to establish clinical phenotypes of DD in persons with chronic HIV. 29 Finally, the cross-sectional nature of the present study does not address the potential evolution of ventricular dysfunction among PLWH and limits our ability to evaluate the future risk of the evolution of incident clinical heart failure. Although future studies of our cohort will focus on monitoring its members longitudinally to investigate the natural history of ventricular dysfunction in this group, a prospectively identified and followed longitudinal cohort is needed to explore and fully characterize the evolution and determinants of cardiac structural alterations in PLWH.…”
Section: Study Limitationsmentioning
confidence: 95%
“…Previous studies have identified nucleoside reverse transcriptase inhibitors (NRTIs) used in conjunction with HIV PIs as responsible for the development of cardiomyopathy in HIV patients (24,25). Presently, there is limited knowledge on the impact of HIV PIs on the development of cardiomyopathy though there is an attempt to 'characterise heart function on antiretroviral therapy' with the introduction of the CHART study (26). These points considered, we sought to investigate the extent and effects of prelamin A accumulation in the setting of cardiomyopathy.…”
Section: Introductionmentioning
confidence: 99%
“…Ряд исследователей выделяют отдельную форму патологии сердца при ВИЧ-инфекции -ВИЧ-ассоциированную кардиомиопатию, связанную с прямым повреждающим действием ВИЧ-инфекции на миокард, сопровождающимся апоптозом кардиомиоцитов и фибробластов [1]. Поражение сердца при ВИЧ-инфекции имеет многофакторный патогенез, характеризующийся не только прямым повреждающим действием, но и влиянием вторичной инфекции, приводящей к развитию мио-, пери-и эндокардитов, применением антиретровирусной терапии, обладающей кардиотоксическим действием [2,3].…”
unclassified
“…Вероятность развития сердечной недостаточности со сниженной систолической функцией левого желудочка (ЛЖ) у ВИЧ-инфицированных больных наступает на 10 лет раньше, чем у пациентов без ВИЧ-инфекции [4]. На фоне антиретровирусной терапии формируется ранняя диастолическая дисфункция (ДД) сердца за счет стимуляции миокардиального фиброза [3].…”
unclassified
See 1 more Smart Citation